Premenstrual Syndrome among Female Students of Colleges in Ujjain City, Madhya Pradesh - Deepika Badkur; Arun Wanjpe; Suchita Singh; Dharmpal Singh Chouhan; Abhinav Sinha (Medsci Publications, 2016)
Objective: To estimate the prevalence and severity of premenstrual syndrome (PMS) and the frequency of contributing symptoms among female students of colleges situated in Ujjain city. Method: Observational follow-up study was conducted at 4 colleges selected by convenience sampling located in Ujjain city. PMS related data from 250 girls (18-25years) who consented to participate was collected using a modified version of daily record of severity of problems for atleast 2 consecutive menstrual cycles. Diagnosis of PMS was made using DRSP criteria and ACOG criteria. Descriptive analysis of data using SPSS version 16.0 was done. Result: The prevalence of PMS was 39.6%. Most common symptoms reported were social withdrawal (77.5%) and headache (77.5%) and most severe symptoms were swollen extremity, anger, social withdrawal and headache in decreasing order of frequency. Conclusion: Frequency of PMS is relatively common in young girls with swollen extremity as most severe symptom reported. A more robust and easily trackable tool to detect PMS is needed.